2018
DOI: 10.1080/1553118x.2018.1448400
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Public Sentiment Toward the Government: How Citizens’ Perceptions of Government Communication Strategies Impact Public Engagement, Cynicism, and Communication Behaviors in South Korea

Abstract: In this study, we explore the relationship between two types of public sentiment toward the government (i.e., public engagement and cynicism) on publics' information transmission behaviors, i.e., megaphoning, about the government. In doing so, we unpack how citizens' perceptions of the communication strategy adopted by the government, as well perceived authenticity of the government's communication impact their sentiments toward the government. An online survey was conducted in South Korea (N = 1112) to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 92 publications
(76 reference statements)
0
8
0
2
Order By: Relevance
“…This study focused on a democratic country and society (Italy), in which citizens are more likely to assume that they have a voice which has some degree of power than those in countries without a democratic tradition (e.g., Wang 2014;Ye et al 2012). While it was outside of the scope of this study to examine the government-citizen relationship, work by Kim and Krishna (2018) found that citizens' perceptions of government communication, both in terms of approach (e.g., bridging or buffering) and authenticity were related to their positive and negative megaphoning behaviors about the government. These findings highlight the practical importance of public sector organizations and governments positively and proactively engaging with citizens when taking on mega-events.…”
Section: Considering the Context: Citizens' Voice And Perception Of Tmentioning
confidence: 99%
“…This study focused on a democratic country and society (Italy), in which citizens are more likely to assume that they have a voice which has some degree of power than those in countries without a democratic tradition (e.g., Wang 2014;Ye et al 2012). While it was outside of the scope of this study to examine the government-citizen relationship, work by Kim and Krishna (2018) found that citizens' perceptions of government communication, both in terms of approach (e.g., bridging or buffering) and authenticity were related to their positive and negative megaphoning behaviors about the government. These findings highlight the practical importance of public sector organizations and governments positively and proactively engaging with citizens when taking on mega-events.…”
Section: Considering the Context: Citizens' Voice And Perception Of Tmentioning
confidence: 99%
“…Apa yang cenderung muncul bukan merupakan upaya persuasif dalam mengajak dan mengedukasi masyarakat, tapi cenderung menonjolkan otoritasnya sebagai kepala daerah dengan gaya komunikasi topdown (Bakir et al 2019;Koa 2018). Padahal, proses komunikasi politik yang terjadi (antara pemerintah dengan masyarakat di sekitar Danau Toba) dapat menjadi momentum bagi pemerintah (Edy Rahmayadi) untuk mendekatkan diri dengan konstituennya (rakyat) (Kim and Krishna 2018;Wardani 2019…”
Section: Metodeunclassified
“…Strategi komunikasi yang digunakan oleh pemerintah akan sangat berdampak pada persepsi publik dan sentimen mereka terhadap pemerintah yang akan berpengaruh kepada opini publik. Oleh karenanya pemerintah perlu memperhatikan bagaimana mereka berkomunikasi dengan warga negara dan bagaimana mereka mengatasi masalah dan kebutuhan warga (Kim, S., & Krishna, 2018). Paparan informasi yang lengkap, diskusi, dan musyawarah yang dilakukan sebelum membu at suatu keputusan dapat meningkatkan kualitas opini publik dan modal sosial yang sangat besar bagi pemerintah dengan mengurangi ketidakpastian dan ambivalensi publik dan dengan meningkatkan partisipasi publik (Hallahan, 2011).…”
Section: Pendahuluanunclassified